SPLENOMEGALY AS A COMPLICATION OF DOGS BABESIOSIS - Dubova, O. A.; Zgozinska, O. A.; Kovalyova, L. O.; Kovalyov, P. V. (Scientific Progress & Innovations, 2019)
Babesiosis is a widely spread blood-protozoan disease of dogs in the Central Polissia region of Ukraine. The causal agents parasitize in the erythrocytes of diseased animals, leading to ruining the former ones. The remains of the ruined cells, the released erythrocytes factors, cause the reaction on the part of lymphoid tissues. Constant pathogenic stress stimulation of the organs of the mono-nuclear phagocytes system, especially the spleen, by the disease pathogens leads to hyperplastic changes – splenomegaly. The purpose of the work is to determine the mechanism of splenomegaly formation for babesiosis and the pathogenic role of the transformed spleen, to establish clinical signs, the state of the organism for this complication, to substantiate recommendations for the treatment of diseased animals. The dogs, suffering from spontaneous babesiosis, complicated by splenomegaly, were investigated. Clinical and laboratory studies were carried out to establish the general condition of the organism functioning of the diseased dogs – hematological and biochemical parameters (hemoglobin content, the number of blood cells, the quality of red blood cells and platelets, erythrocyte sedimentation rate, the level of total and conjugated bilirubin, transaminase activity, creatinine and urea levels) were determined. It was established that babesiosis outbreaks were seasonal with distinct waves in spring (April–June) and autumn (September–October) periods. Complications of babesiosis by splenomegaly were observed, on the average, in 7 % of the diseased dogs. The main number of complications was recorded at the end of the autumn outbreak of babesiosis during the winter period. Thus, splenomegaly is a remote consequence of the pathogen affect and pathological reactions in response to its influence. Clinically, the complication is manifested by increasing the spleen size, perisplenitis. The disorders of the gastro-intestinal tract (diarrhea and constipation), vomiting are caused by the compression effect of the spleen, and often hepatomegaly, which develops in parallel to spleen hyperplasia. Anemia of normochromic type, leukocytosis, accelerated erythrocyte sedimentation rate, megatominae, hypochromia, poikilocytosis (echinocytes, acanthocytes), and fragmented erythrocytes were revealed in the laboratory. Biochemical studies indicate to the completion of inflammation and development of the spleen hyperplasia, inflammatory processes, and also dystrophic changes in the liver, kidney failure that in the complex define the symptom complex of pseudo-hepatorenal syndrome. Hyper-plastically modified spleen is the threat of increasing the unfavorable phenomena of extra-hepatic portal hypertension, compression disorders of the abdominal cavity organs, septic fluidization of the organ. This situation determines the need for splenectomy to preserve the health and life of the animal.